2004
DOI: 10.1295/polymj.36.368
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Rigid Polyurethane Foams with Blowing Agents and Catalysts

Abstract: ABSTRACT:Rigid polyurethane foams (PUFs) were prepared from polymeric 4,4-diphenylmethane diisocyanate (PMDI) and polyether polyol with amine catalyst. Water was used as the chemical blowing agent and, cyclopentane and hydrofluorocarbon (HFC) were used as the physical blowing agents. The kinetic rate of forming the PUF increased with the catalyst and water content. The cell size of the PUF sample decreased with increasing amount of the blowing and gelling catalysts. In the case of the PUF sample blown by water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 4 publications
(6 reference statements)
4
44
0
1
Order By: Relevance
“…The effect of the blowing agent type in apparent density of the foams produced from GCo polyols (Table 1) showed that formulations with physical blowing agents (cyclopentane and n-pentane) produced foams with higher densities than those synthesized with the chemical blowing agent (water). Similar results have been reported in the literature [34][35][36] and this behaviour indicates that smaller cells are formed due to the rapid volatilization of physical blowing agents, which have low boiling point, during the highly exothermic foam growth step in comparison with the CO2, produced by the reaction of water with isocyanate [37]. The effect of blowing agent (water) content in the foams apparent density was also evaluated, as showed in Figure 5a.…”
Section: Resultssupporting
confidence: 84%
“…The effect of the blowing agent type in apparent density of the foams produced from GCo polyols (Table 1) showed that formulations with physical blowing agents (cyclopentane and n-pentane) produced foams with higher densities than those synthesized with the chemical blowing agent (water). Similar results have been reported in the literature [34][35][36] and this behaviour indicates that smaller cells are formed due to the rapid volatilization of physical blowing agents, which have low boiling point, during the highly exothermic foam growth step in comparison with the CO2, produced by the reaction of water with isocyanate [37]. The effect of blowing agent (water) content in the foams apparent density was also evaluated, as showed in Figure 5a.…”
Section: Resultssupporting
confidence: 84%
“…It is believed that infusion of nanoparticles acts as a catalyst to increase the kinetic rate of this chemical reaction. The increased kinetic rate helps the blowing gas to generate gradually and thus giving larger cell size [20].…”
Section: Chemical and Microstructural Propertiesmentioning
confidence: 99%
“…Addition of surfactants or catalysts may affect the size of the cells and also clay nanocomposite is known to be effective to reduce the cell size. [15][16][17] Moreover, clay is expected to reduce the thermal conductivity of gas diffusion since it can lengthen the pathways of gas diffusion. When synthesizing PUF/clay nanocomposites, uniform dispersion of clay is very important to make sure the cells in PUF are small enough.…”
Section: Introductionmentioning
confidence: 99%